Implementation of Indonesian Government Regulations Concerning the Job Loss Guarantee Program in the Province of the Special Capital Region of Jakarta - Rr Ani Wijayati; Haposan Sahala Raja Sinaga (UIN Sunan Gunung Djati, 2024)
The Indonesian government expanded social security for the community, especially those who experienced layoffs or lost their jobs by issuing a Government Regulation to expand social security as amended and adding several provisions to articles in Law Number 40 of 2004 concerning the National Social Security System after the enactment of the Law. Law Number 11 of 2020 concerning Job Creation. The background to the policy is because during the COVID-19 pandemic many companies laid off employment. In Jakarta, the number of people who have lost their jobs has increased. The Central Statistics Agency of Indonesia report released that the number of unemployed people in the Special Capital Region of Jakarta in February 2022 was 410.59 thousand people. This research aims to legally analyze the decisions or beschikking issued by the Jakarta provincial government in implementing the job loss guarantee (JKP) program and analyze the implementation of the job loss guarantee program in the Jakarta. The research method used is a juridical-empirical research method using statutory and case approaches. The results of this research: 1) Decree (beschikking) of the DKI Jakarta Provincial Government in implementing the job loss guarantee program by issuing: Regional Regulation Number 27 of 2012 concerning the Implementation of Employment and Governor's Regulation of the Special Capital Region of Jakarta Province Number 15 of 2023 concerning Amendments to Governor's Regulation Number 55 of 2016 concerning the Implementation of Social Security for Workers through the Employment Social Security Administering Agency. 2) Implementation of PP 37/2021 in the DKI Jakarta Province area, based on employment conditions in February 2023, the working population in Jakarta area was recorded at 4.86 million people and a survey of 135 random respondents related to the dissemination of information about JKP concluded that the implementation JKP, especially in terms of socialization, is still lacking, because as many as 77% admitted that they had never been socialized about the JKP program which has implications for respondents' knowledge of the benefits of the JKP program itself, not many respondents fully know that the benefits of the JKP program are in the form of cash benefits. , benefits of access to job information, and benefits of job training. Of the respondents who knew about the benefits of the JKP program, generally they only knew about the cash benefits, while other respondents admitted that they did not know at all about the benefits of the JKP program. This number of respondents is not small, namely 53 respondents or around 55.8%. The benefits of the JKP program that were known to respondents were benefits in the form of cash as much as 32.7%, benefits from access to job market information as much as 14.7% and benefits from job training as much as 17% and the remaining 55.8% of respondents did not know what the benefits of the JKP program were.